Battery Sustainability of Budget Light-Curing Units. (2022) - Jamalellail, H.MH.; Alshehri, I.M.; Price, R.B.; Al-Zain, A.O.
Abstract : Purpose/Aim: Light-emitting-diode budget light-curing units (LCUs) are classified as medical devices in most countries. These LCUs are required almost every day in most dental offices. Budget LCU manufacturers claim to offer high-quality LCUs that are equivalent to more expensive LCUs, but at a much lower cost. This study assessed the battery performance and the power, irradiance, and radiant exposure values from different budget LCUs over one fully charged battery cycle compared to a more expensive LCU from 3 M. Materials and Methods: Two types of budget LCUs were purchased over the internet; two (LY-A180, NSKI Cordless LCU, China), two (LED Curing Light, BoNew Cordless LCU, China), and compared to a control LCU (Elipar DeepCure-S, 3 M, USA). All LCUs were fully charged, and their power, irradiance, and radiant exposure were measured with a spectrometer [Managing Accurate Resin Curing-Light Collector (MARC-LC), BlueLight Analytics Inc., Canada] over one entire battery life cycle until the battery ran out. The position of each LCU guide tip was standardized over the MARC-LC top sensor at a 0-mm distance. The measurements were collected over a 10 s exposure time with a 30-second interval between each subsequent exposure cycle. The mean values and percent decrease in values were measured. Data were analyzed using two-way ANOVA followed by Tukey post hoc test (p=0.05). Results: The mean power, irradiance, and radiant exposure values from the budget LCUs showed fluctuating readings and an overall decrease in output throughout the battery life compared to the 3 M LCU. The budget LCUs measurement values in the first cycle measured mean power values from 205-444 mW, mean irradiance from 533-1154 mW/cm 2, mean radiant exposure 5.3-11.5 J/cm 2 . The total number of exposure cycles from the budget LCU ranged from 326-764 cycles. The decrease in mean power, irradiance, and radiant exposure from the budget LCUs ranged from 24-81%. The control 3 M LCU delivered 906.3 mW, 1427.9 mW/cm 2, and 14.3 J/cm 2 in the first cycle and completed 959 exposures cycles. There was a slight 4.9% increase in mean power, irradiance and no changes in its radiant exposure values. Significant differences in measurements were observed among all the budget units except between one NSKI Cordless and one BoNew Cordless LCU. Conclusions: The light output from the budget LCUs tested from the same and from different manufacturers was inconsistent. These lights were unable to sustain their power, irradiance, and radiant exposure output values. These values were significantly lower than the control LCU.